The Importance of Instilling an Entrepreneurial Soul in Primary School Age Children in The Face of The Digital Era - Frisky Ramadhani; Anisatun Chasanah; Lin Wahyuni (Universitas Sebelas Maret, 2019)
Entrepreneurship is an ability in terms of creating business activities as contained in Law no. 20 of 2003 concerning the National Education System, that education is expected to be able to achieve the formation of cognitive (intellectual) aspects of affective (mental or moral) and psychomotor (skill) aspects. To instill an entrepreneurial spirit in elementary school age children, it is better to use concrete or concrete examples that are in accordance with Piaget's opinion that children at the age of 7-12 years enter the concrete operational stage, where children will easily understand material or knowledge if children are confronted with something or real conditions. When children enter education in elementary schools, entrepreneurship is used to prepare for the economic challenges of the Industrial Revolution era, which requires that future generations can keep up with the times, especially in terms of digital technology.